Pengaruh Praktik Kerja Industri Terhadap Kompetensi Siswa Teknik Instalasi Tenaga Listrik di Sekolah Menengah Kejuruan - Yusrizal, Firman; Usmeldi, Usmeldi (Jurnal Pendidikan Teknik Elektro, 2024)
This research is motivated by industrial work practices on the competence of class XII students with a significant influence. The aim of this research is to determine the influence of industrial work practices on the competency of class XII Electrical Power Installation Engineering students at SMK Negeri 1 West Sumatra. This research uses a quantitative approach with an associative type of research. The subjects of this research were class XII students in Electrical Installation Engineering at SMK 1 West Sumatra. The type of data and data collection is in the form of a questionnaire and data analysis uses the successive interval (MSI) method. The results of the research showed that industrial work practices had a significant impact on student competency in learning electrical power installation techniques. The research suggestions are: 1) Students are expected to optimize lessons at school by following industrial work practices so that they can increase student competency in learning. 2) Teachers are expected to always develop industrial work practice learning programs so that they can have a positive impact on students' learning competencies. 3) Future researchers are expected to be able to study and research further about different industrial work practices and student competencies so that they can provide more references in further research and consider using a longer research design, allowing long-term observations of the impact of industrial work practices on student competencies.